Construct - Priemus, Jessica (2014)
Construct is a fourteen-piece capsule collection that examines the relationship that exists between the designer, artisan, wearer and garment. The abstract graphics are derived from patterns of weaving and construction – connecting the wearer to the garment and its origin. Intricate embroidery and appliqué designs represent the history and fabric of each garment and the memories of making.